Linking Avicennia germinans (Acanthaceae) architecture to gall richness and abundance in Brazilian Amazon mangroves. (11th August 2017) - Silva, Luzinete L.; Santos, Rita C. O.; Fernandes, Marcus E. B.
Abstract: The diversity and abundance of gall‐inducing organisms are directly proportional to the structural complexity of the host plant. This hypothesis is controversial for forest environments, such as mangroves. Avicennia germinans (L.), a principal mangrove tree species found in the Neotropical region, is considered to be a superhost for gall‐inducing insects. Using a generalized linear mixed model (GLMM) based on the analysis of 1000 apical branches from 50 A. germinans trees, we examined the diversity and abundance of gall morphotypes (GM), together with the structural attributes of replanted 5‐ to 9‐year‐old mangroves, in the Amazon coast of Brazil. A total of 7602 galls were registered, averaging 1.3 ± 0.4 galls per leaf. Sixteen of the 22 morphotypes identified were found at all study sites. Two gall morphotypes (GM7 and GM4) were the most abundant, representing approximately 40 percent of the total. The structural complexity of the plant (mainly based on the number of leaves) directly affected the abundance and diversity of these organisms. While A. germinans is a superhost, this type of parasitism did not affect plant development or survival. The ample distribution of A. germinans, the formation of monospecific forests, and the high palatability of this plant make it an essential resource for the survival of the gall‐inducing guild in the mangroves of the Neotropics.